Biodiversidade de nematoides parasitos de peixes da Amazônia Brasileira - REIS, Maria Helena dos Santos (2022)
The Brazilian Amazon Biome occupies more than 49% of the national territory distributed in nine states and has an extremely vast socio-biodiversity, providing the country with strategic wealth. This area, despite having great ecological importance and being subject to strong anthropic pressures, is relatively little studied. In this sense, the present Master's Thesis was concerned with generating basic information about the parasitic nematode fauna associated with fish from the Brazilian Amazon Biome, as it corresponds to a subject of great relevance, since some species represent a problem for fish, have zoonotic potential and constitute public health problems. The results of the present study were condensed into three chapters: the first chapter is related to the literature review from 2010 to 2021 that allowed the publication of the new annotated checklist of fish parasitic nematodes for the Brazilian Amazon, including comments on hosts, geographic location and site of infection of the parasites. The results of this scientific work correspond to an updated list of fish parasitic nematode species, described and recorded for the Amazon biome in the last 10 years. The second chapter is a scientometric review about the advances in knowledge about fish parasitic nematodes in the Brazilian Amazon region, generated between the period 1940 to 2021. The results of this scientific work showed gaps with regard to studies with parasitic nematodes of fish with importance for Public Health in the Brazilian Amazon region. Annex 1 is a part of the results obtained from a pilot collection carried out at the beginning of the pandemic, where the crustacean Dolops intermedia Silva, 1978 is being recorded for the first time in Maranhão, in new hosts. In addition, new morphological and ecological data for this species are provided.